(untitled) (Perner’s Contacts, 2012)
This paper discusses the problems of low emission zones in Europe. Currently in Europe there are more than 270 low-emission zones, in which is limited entrance or entrance is charged for some vehicles. The aim of this paper is to highlight the changes in the low emission zones, which occurred at the end of 2011, respectively with effect from January 2012.